Abu Yazid (Ittihad) dan al Hallaj (Hulul) - R, Rusdin; Santalia, Indo; Amri, Muh. (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Sufism as a scientific field also experienced controversy and polemics in its long history of struggles and struggles until it became established and gave birth to the congregations that they are today. In the long journey of Sufism, almost the majority of Islamic scholars and intellectuals agree that the existence of Sufism has existed since the time of the Prophet. which most Muslims recognize as a scientific field of spiritual conditioning, or the bonding of human relationships with God. Sufism has developed from time to time. From being limited to morals to expanding into the realm of faith, giving rise to many pros and cons. Ittihad and Hulul are two of the theories of Sufism that have raised many pros and cons among Islamic scholars since their inception until today. What is meant by Ittihad is a level in Sufism where a Sufi feels himself united with God; a level where the lover and the beloved have become one, so that one of them can call the other with the words: Hi Me. Meanwhile, Hulul is a teaching which states that God has chosen certain human bodies to reside in them with their divine qualities, after the human qualities in their bodies have been eliminated first.